Comparative effects of gamma and electron beam irradiation on the antioxidant potential of Portuguese chestnuts (Castanea sativa Mill.) - Carocho, Márcio (2012)
Chestnuts (Castanea sativa Mill.) are widely consumed all over the world, and have been recently studied for their antioxidant potential. The present study reports the effect of e-beam and gamma radiation (doses of 0, 0.5, 1 and 3 kGy) on the antioxidant potential of Portuguese chestnuts. Irradiation might be an alternative preservation method, since Methyl Bromide, a widely used fumigant, was banished by the European Union in 2010 due to its toxicity. The antioxidant activity was evaluated through 2,2- diphenyl-1-pycrylhydrazyl (DPPH) free radical scavenging activity assay, reducing power by the Ferricyanide/Prussian blue assay, and lipid peroxidation inhibition by β- carotene/linoleate and thiobarbituric acid reactive substances (TBARS) assays. The analysis of total phenolics and flavonoids was performed by spectrophotometric assays. Irradiated samples preserved total phenolics content (but not flavonoids) and revealed higher antioxidant activity (lower EC50 values) than the control samples. The most indicated doses to maintain antioxidants content, and to increase antioxidant activity were 1 kGy and 3 kGy for electron beam and gamma radiation, respectively.